Self-activation is a two-edged sword: The effects of I primes on cooperation - Utz, Sonja (Journal of experimental social psychology, 2004)
Two studies examined the influence of I primes on cooperative behavior. Two contrasting hypotheses were tested, using prosocial allocations (Experiment 1) and behavior in a give-some dilemma (Experiment 2) as dependent variables and assessing subjects’ social value orientation. The self-activation hypothesis ( Verplanken & Holland, 2002) predicts that social value orientation influences behavior to a stronger degree when activated. That is, proselfs should behave less cooperatively, whereas prosocials should behave even more cooperatively in an I prime condition. The independent self-construal hypothesis (e.g., Gardner, Gabriel, & Lee, 1999) predicts a stronger concern for one’s own outcome and less cooperative behavior for individuals with an activated independent self-construal. In both studies an interaction between priming and social value orientation occurred, supporting the self-activation hypothesis. Implications for the importance of social cognitive processes underlying cooperative behavior, as well as, implications for research on independent vs interdependent self-construals are discussed.